Pengampunan pajak (tax amnesty) sebagai upaya optimalisasi fungsi pajak - Kusuma, Agus Iwan (INOVASI, 2016)
Tax Amnesty program could be obtain additional state revenues from taxes due to the addition of the object and new tax payer that has not previously been identified, it calls as budgetary function of tax. Apart from that, tax amnesty is also intended to increase the compliance of the taxpayer, the objectives to be achieved by the tax amnesty could be categorized as a regulatory function. On Redistribution and democracy function, tax collected on the tax amnesty program will be used to provide public goods and services. Keyword: Tax amnesty; Budgetary; Regulatory; Redistribution; Democracy; TaxPayer